Preprocedural imaging guiding ventricular tachycardia ablation in structural heart disease - Ferreira, Afonso Nunes (2024)
© 2024 The Author(s). Journal of Arrhythmia published by John Wiley & Sons Australia, Ltd on behalf of Japanese Heart Rhythm Society. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.